Rotary dryer for drying salt, Hutchinson, Kansas (Underwood & Underwood)
View of a worker examining a rotary dryer for drying salt at an unknown facility in Hutchinson, Kansas. This photograph is one of a set of six stereographs detailing the mining and production of salt.
Keywords: Employees; Manufacturing industries; Salt industry and trade; Salt mines and mining